Cratoxylumxanthone C, a natural xanthone, inhibits lung cancer proliferation and metastasis by regulating STAT3 and FAK signal pathways - Li, Yeling; Wang, Huimei; Liu, Wenhui; Hou, Jiantong; Xu, Jing; Guo, Yuanqiang; Hu, Ping (Frontiers in Pharmacology, 2022)
To obtain bioactive natural products as lead compounds for cancertreatment, cratoxylumxanthone C, a natural xanthone was obtained from Cratoxylum cochinchinense (Lour.) Bl., which has not been reported on its anti-tumor effects in vivo and in vitro. Our study revealed that cratoxylumxanthone C had significant anti-tumor activity by inducing cell apoptosis, increasing ROS production, and arresting cell cycle at G0/G1 stage. The mechanic examination showed cratoxylumxanthone C inhibited A549 cell proliferation and migration via regulating STAT3 and FAK signaling pathways. Furthermore, it inhibited cell proliferation and migration in a zebrafish xenograft model, and inhibited tumor angiogenesis in zebrafish in vivo. Collectively, these cellular and zebrafish results suggested that cratoxylumxanthone C may be considered as an anticancer agent for lung cancer, especially non-small cell lung cancer (NSCLC).